1
$\begingroup$

If I have the following triangle:

Where $\angle B=\angle C = O$
And $AP$ bisects $\angle A$ so essentially $\angle BAP = \angle CAP = \frac12 \angle A$
We can prove that $\angle APB = \angle APC$ but how do we show that they are 90 degrees?

$$ \angle APB + \frac12 \angle A + \angle ABC = 180^\circ = \angle ABC + \frac12 \angle A + \angle APC $$

So:

\begin{align} \angle ABP &= 180^\circ - \left( \angle ABC + \frac12 \angle A \right) \\ \angle APC &= 180^\circ - \left( \angle ABC + \frac12 \angle A \right) \\ \end{align}

So $\angle ABP = \angle APC$ but is it also proven that they are 90 degrees? How?

enter image description here

$\endgroup$
3
  • 1
    $\begingroup$ Since BC is a straigth line, $\angle APB + \angle APC = 180$ $\endgroup$ May 27, 2016 at 17:16
  • $\begingroup$ @AlainRemillard:Yes but that does not prove that each is 90 degrees right? $\endgroup$
    – Jim
    May 27, 2016 at 19:53
  • $\begingroup$ Combine with the fact that $\angle APB = \angle APC$, it does $\endgroup$ May 27, 2016 at 21:25

1 Answer 1

2
$\begingroup$

First we write a formula for the sum of the angle measures of triangle PAB. I'm going to just use "APB" as "angle APB". We note that angle ABP is "O": $$O + \frac{A}{2} + APB = 180$$ Next we write a formula for the sum of the angle measures of triangle ABC: $$2\cdot O + A = 180$$ This gives you that $$O = \frac{180-A}{2}.$$ We substitue this value for "O" in the formula for triangle PAB: $$\frac{180-A}{2}+\frac{A}{2} + APB = 180$$ $$90 - \frac{A}{2}+\frac{A}{2}+APB = 180$$ $$90 + APB = 180$$ $$APB = 90.$$

We can do the same thing for APC, using triangle PAC in place of triangle PAB.

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .